Financial Distress Risk Levels of Listed Small and Medium Enterprises in the Philippines - Rago, Gensbergh G.; Gabriel, Sarah Fe Sharon L.; Abellar, Jonas B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Small and Medium Enterprises (SME) play a significant role in the Philippine economy in terms of promoting entrepreneurship and technological innovation, encouraging local development and alleviate poverty levels. However, SMEs are more susceptible to financial constraints and difficulties attributable to limited access to capital and weak financial management practices, among others, which lead to financial distress and insolvency in the long run. Anchored on the Early Bankruptcy Theory, a company’s financial distress can be at-tributed to its inability to meet its obligations which stem from poor management, low profitability, inadequate cash flow, or excessive leverage, among others. Hence, the Study aimed at describing and determining the financial dis-tress risk levels of sample SMEs in order to provide valuable insights into the financial health and stability of these companies. Specifically, the Study ascertained the nature, determinants and levels of financial distress risks using the Altman Z-Score Model (1968). Based on the result, sample companies at SAFE levels were deemed to have strong financial positions with good profitability, liquidity, leverage, and solvency while sample companies at DISTRESS levels could experience financial difficulties with lack of liquidity, declining revenues, and reliance on debt financing from third parties. Future research can (1) expand the determination of financial distress risk levels into non-listed SMEs and other listed companies from key sectors using a longer time frame to assess changes in the financial distress risk levels resulting from changes in economic conditions and (2) investigate the impact of financial ratios on financial distress risk while also considering corporate governance measures affecting it.